Protein not limiting factor in ruminant growth - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
A new study carried out in Tanzania has concluded that energy intake is the major limiting factor in the growth of ruminants on semi-arid grasslands in that country, and that, contrary to longheld belief, protein supplements alone are not effective...